2016
DOI: 10.1080/08820538.2016.1208760
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Return to the Operating Room after Resident-Performed Cataract Surgery

Abstract: Phacoemulsification done by a junior resident or using the divide-and-conquer technique had the highest risk of reoperation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Numerous studies have sought to measure the learning curve in resident surgeries using parameters such as operative time, [4][5][6][7][8] intraoperative complications, [8][9][10][11][12][13][14] direct supervisor interventions, 9,10 visual outcomes, 8,14,15 and return to the operating room. 16,17 These studies demonstrated that increased surgeon experience corresponded to a decrease in these parameters. In a chart review of 680 cases, the adjusted phacoemulsification time and vitreous loss rate were significantly decreased when comparing the first 80 cataract surgeries of residents with the 81st to 207th surgeries.…”
Section: Introductionmentioning
confidence: 91%
“…Numerous studies have sought to measure the learning curve in resident surgeries using parameters such as operative time, [4][5][6][7][8] intraoperative complications, [8][9][10][11][12][13][14] direct supervisor interventions, 9,10 visual outcomes, 8,14,15 and return to the operating room. 16,17 These studies demonstrated that increased surgeon experience corresponded to a decrease in these parameters. In a chart review of 680 cases, the adjusted phacoemulsification time and vitreous loss rate were significantly decreased when comparing the first 80 cataract surgeries of residents with the 81st to 207th surgeries.…”
Section: Introductionmentioning
confidence: 91%
“…By doing clinical audit we calculate some important facts that are usually missed like steps of surgery, instruments used and time taken. [18][19][20][21] So, for the betterment of surgical outcomes, audit and re audit should be conducted. [22][23][24][25] Postoperative VA was recorded for 982 (100%) eyes.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical trainingincluding length of training-predicts performance and outcomes, though not necessarily transferability, across subspecialties. [28][29][30][31][32][33][34] Limitations of this study include the small number of residents assessed (n ¼ 12) and differences in oculoplastic training. Early in the years of this retrospective chart review, residents did not have an immersive oculoplastic training period.…”
Section: Discussionmentioning
confidence: 99%